Who wants Arthur? - Graham, Amanda; Gynell, Donna (Milwaukee : G. Stevens Pub., 1984)
Arthur, a dog in a pet store waiting to be adopted, takes on the identities of other animals he thinks might be more appealing, until discovering that he can be a success as himself.
Rev. ed. of: Arthur.
Keywords: Dogs; Pets; Individuality